External relationships as implementation determinants in community-engaged, equity-focused COVID-19 vaccination events - Moore, Ramey; Callaghan-Koru, Jennifer; Vincenzo, Jennifer L.; Patton, Susan K.; Spear, Marissa J.; Riklon, Sheldon; Alik, Eldon; Padilla Ramos, Alan; Takamaru, Stephanie; McElfish, Pearl A.; Curran, Geoffrey M. (Frontiers in Health Services, 2024)
Background While relationships and connectedness among organizations have been included in implementation theories, models, and frameworks, the increased attention to health equity in implementation science raises the urgency of understanding the role of relationships external to the implementing organization. This paper addresses this gap through an exploration of the role of external relationships in community-based, equity-focused interventions. Methods This study focuses on an equity-focused, community-based COVID-19 vaccination intervention in Arkansas, drawing upon long-term community-engaged relationships among University of Arkansas for Medical Sciences and the Hispanic and Marshallese Islander communities. We used an exploratory qualitative descriptive design to examine barriers and facilitators to implementation of COVID-19 vaccination events analyzing in-depth qualitative interviews with implementation team members (n = 17). Results All participants described pre-existing relationships among the implementing organization, partner organizations, and communities as a key implementation determinant for this equity-focused program. At the inter-organizational level, external relationships included formal connections and informal relationships among staff (e.g., communication channels from prior partnerships). At the individual level, strong external relationships with the community were facilitators leveraging long-term engagement, community familiarity, and staff from the communities of focus. Strong external relationships facilitated program reach in underserved communities through three mechanisms: (1) reduced time required to establish functional working relationships among partners; (2) accessibility and cultural congruence of health services; and (3) increased trust among community members. Barriers to implementation also existed in external relationships, but had less influence than facilitators. Conclusions Achieving health equity in implementation science requires greater understanding of external relationships as implementation determinants. This exploratory study makes a significant contribution to the literature by describing the types of external relationships that facilitate equitable implementation and identifying the mechanisms through which they may work. We argue that approaches to community engagement drawn from community-engaged research approaches may be useful, as these processes require investment in building/maintaining formal and informal organizational and interpersonal relationships. Further research is needed to understand connections among external relationships and other implementation determinants.